Small and Long Regulatory RNAs in the Immune System and Immune Diseases - Stachurska, Anna; Zorro, Maria M.; van der Sijde, Marijke R.; Withoff, Sebo (Frontiers in Immunology, 2014)
Cellular differentiation is regulated on the level of gene expression and it is known that dysregulation of gene expression can lead to deficiencies in differentiation that contribute to a variety of diseases, particularly of the immune system. Until recently, it was thought that the dysregulation was governed by changes in the binding or activity of a class of proteins called transcription factors. However, the discovery of micro-RNAs and recent descriptions of long noncoding RNAs have given enormous momentum to a whole new field of biology: the regulatory RNAs. In this review, we describe these two classes of regulatory RNAs and summarize what is known about how they regulate aspects of the adaptive and innate immune systems. Finally, we describe what is known about the involvement of micro-RNAs and long noncoding RNAs in three different autoimmune diseases (celiac disease, inflammatory bowel disease, and multiple sclerosis).